In vitro production of insulin-responsive skeletal muscle tissue from mouse embryonic stem cells by spermine-induced differentiation method - Saito, Mikako; Ishida, Ayano; Nakagawa, Shota (Human cell : official journal of Human Cell Research Society, 2017)
The treatment of an embryoid body with spermine for a short duration can trigger the generation of a 3-dimensional multilayer myotube sheet (MMTS) that shows pulsatile activity. MMTS was previously characterized as a model of skeletal muscle tissue. In the present work, the insulin responsiveness of MMTS was investigated because it is an essential function for a model of skeletal muscle. The glucose uptake activity of MMTS was analyzed by confocal microscopy using fluorescent glucose analogs, namely 2-[ N -(7-nitrobenz-2-oxa-1,3-diazol-4-yl)amino]-2-deoxy- d -glucose (2-NBDG) and its l -glucose counterpart, 2-NBDLG. The specific uptake rate of glucose was estimated from the difference between the fluorescent signals of 2-NBDG and 2-NBDLG. It was enhanced by insulin stimulation to 3.6 times higher than the control without insulin, and this insulin responsiveness was maintained for 5 days. The advantages of the 3-dimensional structure of MMTS are discussed in the contexts of its potential in vivo and in vitro uses.